Is the Feldstein-Horioka Puzzle Really a Puzzle? - Daniel Levy (Aspects of Globalisation: Macroeconomic and Capital Market Linkages in the Integrated World Economy, 2004)
Using the framework of a dynamic intertemporal optimization model of an open economy, it is shown that the long-run investment-saving correlation follows directly from the economy's dynamic budget constraint and this does not depend on the degree of international capital mobility. Therefore, unless the budget constraint is violated, the time series of investment and saving should be cointegrated, and this should be true for any degree of capital mobility. Using an improved econometric technique, which encompasses the tests used by previous authors and avoids some of the pitfalls associated with their tests, I show that their conflicting findings can be explained by a simple but important, omitted variables problem. Using annual and quarterly post-war U.S. data, I find that investment and saving are cointegrated in levels as well as in rates, regardless of the time period considered, as predicted by the model.
Keywords: F21; F32; F02; F41; 330; Feldstein-Horioka Puzzle; Capital Mobility; Investment-Saving Correlation; Dynamic Budget Constraint; Integration and Cointegration; Omitted Variables